Judicial jurisprudence issued by Sharia courts in family reform - Baklizi, Waleed Khaled (Journal of Economic, Administrative and Legal Sciences, 2023)
In light of the efforts of the Chief Justice Department to continuously update and develop the legislation governing the work of the department and the Sharia courts, the Sharia Procedure Law No. 31 of 1959 and its amendments up to 2016 were amended, which contained several amendments, the most important of which was the establishment of offices for reform, mediation and family conciliation. And since the family reform offices are new in the Jordanian Sharia judiciary, they formed a fertile ground for Sharia court rulings and jurisprudence, in terms of understanding and application. This research came to collect these jurisprudences, and dealt with them with statement and analysis, with mention of the evidence that was relied upon. To show its importance in family reconciliation between the parties to the lawsuit in general, and reconciliation between the spouses in particular, in line with and complementary to what Islamic law decided to preserve the family with a sound upbringing; Because of its direct impact on the security of the Islamic community as a whole. This study dealt with the concept of jurisprudence issued by Sharia courts, the judge’s discretion in transferable cases for family reform, and the most important jurisprudence issued by Sharia courts in family reform. In the conclusion, he mentioned the most important results that were reached, the most important of which are: that the occurrence of the difference in the jurisprudence of the courts of the second degree is due to the difference in understanding the texts of the law and the mechanism of its application. Among the most important recommendations: Work to unify the jurisprudence issued by the Sharia courts regarding family reform, by working to pay attention to the drafting of legal texts, so that the meaning of the text is as clear and visible as possible, and to distance itself from problematic texts. To narrow the scope of interpretation of texts as possible.